Pengaruh Pajak dan Kualitas Audit terhadap Transfer Pricing - Ambarita, Dinar; Rahmadania, Siti Aisyah Nurrizqi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This research aims to investigate the effects of Audit Quality and Audit Cost on Transfer Pricing. This research analyzed the financial accounts of international corporations listed on Bursa Efek Indonesia (BEI) from 2018 to 2022. This research employed a purposive sampling method to gather data from 19 international firms listed on Bursa Efek Indonesia between 2018 and 2022. This study utilizes second-level financial statements from each organization in the research sample. This study employs the following independent variables: Pay (X1), Audit Quality (X2), and Transfer Pricing (Y) as the dependent variable. The current study employs the panel data regression methodology. This article evaluates the research outcomes utilizing the Eviews 10 Student Version Lite crack. The research determined that the optimal model is the Fixed Effect Model (FEM). The findings of this study indicate that Pajak exerts a partial influence on transfer pricing, however audit quality does not demonstrate a partial effect on transfer pricing. Nonetheless, when both elements are concurrently considered, they exert a cumulative influence on Transfer Pricing.